Modern pedagogical aspects in the context of improving physical and psychological health: a comprehensive analysis - Lesia Korobeinikova; Georgiy Korobeynikov (Pedagogy of Health)
Background and Study Aim. Modern education increasingly integrates pedagogical methods to enhance both the academic achievements and overall well-being of various population groups. Despite these efforts, challenges remain in effectively applying these approaches to improve health outcomes. The purpose of this study is to analyze contemporary pedagogical approaches and their effectiveness in the context of improving physical and psychological health based on a review of scientific publications.